Genomic variation in two gametocyte non-producing Plasmodium falciparum clonal lines. (December 2016) - Campino, Susana; Benavente, Ernest; Assefa, Samuel; Thompson, Eloise; Drought, Laura; Taylor, Catherine; Gorvett, Zaria; Carret, Celine; Flueck, Christian; Ivens, Al; Kwiatkowski, Dominic; Alano, Pietro; et al.
Abstract Background Transmission of the malaria parasitePlasmodium falciparum from humans to the mosquito vector requires differentiation of a sub-population of asexual forms replicating within red blood cells into non-dividing male and female gametocytes. The nature of the molecular mechanism underlying this key differentiation event required for malaria transmission is not fully understood. Methods Whole genome sequencing was used to examine the genomic diversity of the gametocyte non-producing 3D7-derived lines F12 and A4. These lines were used in the recent detection of thePF3D7_1222600 locus (encoding PfAP2-G), which acts as a genetic master switch that triggers gametocyte development. Results The evolutionary changes from the 3D7 parental strain through its derivatives F12 (culture-passage derived cloned line) and A4 (transgenic cloned line) were identified. The genetic differences including the formation of chimericvar genes are presented. Conclusion A genomics resource is provided for the further study of gametocytogenesis or other phenotypes using these parasite lines.